Preserving of Hornbill Bird through 3-Dimensional Animation Clips - Cahyadi, A T; Fadillah, R; Mulyana, H; Ramdan, Z F (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Post-Covid-19 pandemic conditions, the use of digital technology in animation and multimedia can produce works that can be used as a solution to existing problems, especially in the conservation of the Indonesian Borneo hornbill. The design in the form of a film or animation clip aims to educate the importance of hornbill conservation. The method used in this study uses a qualitative descriptive method with data collection and data processing, in the technical implementation of the animation pipeline, namely the stages of pre-production, pre-production, and post-production. The results of this study have succeeded in using these stages and producing a video or animation clip entitled The Spirit of Ampong with three-dimensional techniques. It is hoped that the results of the design will have a positive impact on the conservation of the hornbill.